People's Republic of China-Hong Kong Special Administrative Region : Staff Report for the 2005 Article IV Consultation Discussions. (IMF Staff Country Reports; Country Report, 2006)
The staff report for the 2005 Article IV Consultation on the People's Republic of China highlights economic developments and fiscal policy. The continued robust growth owes much to the favorable external environment, with judicious macroeconomic policies, continued structural reforms, and the confidence-building effects of the Closer Economic Partnership Arrangement (CEPA). Reflecting the buoyant activity, inflation has picked up mildly, but remains well contained. Executive Directors noted that low-income families adversely affected by the tax could be assisted through targeted transfers.